2002
DOI: 10.1177/159101990200800408
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pure Spontaneous Subdural Haematoma from Ruptured Intracranial Aneurysms

Abstract: Acute subdural haematoma (ASDH) is rarely caused by an aneurysmal rupture. We report four cases of pure acute subdural haematomas caused by ruptured intracranial aneurysms. Aneurysms were localized in the posterior communicating artery in two cases, in the anterior communicating artery in one case and in the middle cerebral artery in one other case. Possible mechanisms for this type of aneurysmal bleeding are discussed. A good prognosis for these patients can be expected with rapid evacuation of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…An additional 40 similar cases of pure subdural haematoma caused by intracranial aneurysm have been reported since 1980 (Table 1). [3][4][5][6][7][8] The average age at presentation was 46.6 years, with 27/41 patients (65.9%) being female. The site of aneurysm included ICA-posterior communicating artery (PcomA; 16 cases, 39.0%), MCA (10 cases, 24.4%; including the present case), anterior communicating artery (AcomA; six cases, 14.6%), distal ACA (four cases, 9.8%) and other sites (five cases, 12.2%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 40 similar cases of pure subdural haematoma caused by intracranial aneurysm have been reported since 1980 (Table 1). [3][4][5][6][7][8] The average age at presentation was 46.6 years, with 27/41 patients (65.9%) being female. The site of aneurysm included ICA-posterior communicating artery (PcomA; 16 cases, 39.0%), MCA (10 cases, 24.4%; including the present case), anterior communicating artery (AcomA; six cases, 14.6%), distal ACA (four cases, 9.8%) and other sites (five cases, 12.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of this condition can lead to delays in diagnosis and treatment, as occurred in the present case. 4,7,26,30,31 In addition, the mild symptoms (which may occur several days before admission) are unusual for aneurysm rupture, and intracranial aneurysm bleeding is often ruled out in the absence of subarachnoid haemorrhage. Aneurysm rupture should be strongly considered, however, if a patient presents with a pure subdural haematoma without history of trauma or coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, aneurysm rupture may accompany acute subdural hemorrhage (SDH) 15). However, pure SDH occurring without detectable SAH is very unusual 2)13). We report a case of pure SDH secondary to internal carotid artery (ICA) dorsal wall aneurysm rupture.…”
Section: Introductionmentioning
confidence: 95%
“…Aneurysm rupture usually presents as a subarachnoid hemorrhage (SAH), often in combination with intracerebral hemorrhage (ICH) and extension into the ventricle (intraventricular hemorrhage, IVH) (Barton and Tudor 1982 ; Mansour et al 2014 ). In rare cases, acute subdural hematoma (aSDH) combined with SAH due to aneurysm rupture has been reported (Biesbroek et al 2012 , 2013 ; Kocak et al 2009 ; Marbacher et al 2010 ; Nozar et al 2002 ), with only a few cases reported since the first case was reported in 1855 (Kocak et al 2009 ; Marbacher et al 2010 ). According to the literature, the incidence of aSDH due to aneurysmal rupture varies from 0.5 to 22 % (Barton and Tudor 1982 ; Biesbroek et al 2012 ; Marbacher et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%